Comparative analyses across cattle genders and breeds reveal the pitfalls caused by false positive and lineage-differential copy number variations - Zhou, Yang; Utsunomiya, Yuri T. [UNESP]; Xu, Lingyang; Hay, El Hamidi Abdel; Bickhart, Derek M.; Sonstegard, Tad S.; Van Tassell, Curtis P.; Garcia, Jose Fernando [UNESP]; Liu, George E. (Springer Nature, 2016)
We compared CNV region (CNVR) results derived from 1,682 Nellore cattle with equivalent results derived from our previous analysis of Bovine HapMap samples. By comparing CNV segment frequencies between different genders and groups, we identified 9 frequent, false positive CNVRs with a total length of 0.8 Mbp that were likely caused by assembly errors. Although there was a paucity of lineage specific events, we did find one 54 kb deletion on chr5 significantly enriched in Nellore cattle. A few highly frequent CNVRs present in both datasets were detected within genomic regions containing olfactory receptor, ATP-binding cassette, and major histocompatibility complex genes. We further evaluated their impacts on downstream bioinformatics and CNV association analyses. Our results revealed pitfalls caused by false positive and lineage-differential copy number variations and will increase the accuracy of future CNV studies in both taurine and indicine cattle.